Atlas of the forest sector in Poland - Gerasimov, Yuri (Finnish Forest Research Institute, 2013)
This atlas is a collection of maps with a short description of the current situation of the forest sector in Poland including the regions of Dolnośląskie, Kujawsko-pomorskie, Lubelskie, Lubuskie, Łódzkie, Małopolskie, Mazowieckie, Opolskie, Podkarpackie, Podlaskie, Pomorskie, Śląskie, Świętokrzyskie, Warmińsko-mazurskie, Wielkopolskie, and Zachodniopomorskie. The cartographic information covers forest resources, silviculture, wood harvesting, production and the most important producers of wood-based products (sawnwood, plywood, wood-based panels, pulp, paper, paperboard), potential of energy wood, producers of forest-related machinery, wood pellets and briquettes, forest education, and research institutions. This review serves the information needs of different stakeholders and those interested in the forest sector of Poland.
Layout: Anne Siika/Metla
Keywords: bioenergia; metsäpolitiikka; metsäteollisuus; metsävarat; puunkorjuu; bioenergy; forest industry; forest policy; forest resources; wood harvesting